Consumer Innovativeness in Consumer-Company Relationship and Mediating Role of Consumer Value: An Empirical Study of Cell Phone Users in Pakistan - Shahid Rasool; Asif Ayub Kiyani; Fadilah Binti Siali; Hiram Ting; Mahani Mohammad Abdu Shakur (International Review of Management and Marketing, 2017)
The aim of this study is to find out the relationship between the company image, company trust, consumer value and consumer innovativeness behavior. It focuses on how the company image and company trust influence the consumer value and consumer innovativeness behavior with respect to consumer independent judgment making and consumer novelty seeking. The research design of the study was cross-sectional and exploratory. The data were collected through a questionnaire from university students who were cell phone users. Consumer value has partially mediated between company image, company trust and consumer innovativeness behavior. The results showed the significant impact of company image and company trust on consumer innovativeness behavior rather than consumer value. Marketing manager and policy makers are willing to pay much attention to increase to the maximum consumers of their company’s products. Cell phone companies demand young buyers who are frequently changing their cell phones. Hence, this study gives a new aspect to enhance the cell phone consumer with the help of increasing the company image and company trust, instead of focusing on consumer values.